Komunikasi Sosial Etnis Bali Dalam Menjaga Kerukunan Di Tengah Masyarakat Multikultur Dusun Sengkongo Desa Kuranji Kecamatan Labuapi Kabupaten Lombok Barat - Ni Wayan Wahyu Ekawati (Sadharananikarana: Jurnal Ilmiah Komunikasi Hindu, 2021)
Society is a manifestation of human life together, process of social life takes place in society, the process is either between relationships or between actions. In society as an institution, human life takes place as well as the whole process of development of people's lives as a place and field where the inter-action takes place as a manifestation of its citizens with all the characteristics and character in a social phenomenon and certain manifestations or overall socio-psychological. Research on Bali ethnic communication in maintaining harmony in a multicultural society in Sengkongo hamlet aims to find forms of inter-religious harmony. The location of the research is conducted in the Sengkongo hamlet of Kuranji village, West Lombok regency, with the subjects are Balinese and Sasak ethnic, and the object of research is religious harmony. The problem in this study is to find Balinese ethnic social integration in carrying out ancestral cultural heritage, Balinese ethnic communication strategies in establishing harmony of life, the implications of Balinese ethnic communication in building social life of diversity in Sengkongo hamlet. This research is qualitative descriptive, the results of the research are described in sentences instead of numbers. Theories used in this study are politeness theory, interactional conventional theory, structural functional theory. Data collection uses observation, interviews, and documentation. Data analysis is in the form of data reduction, data presentation, data conclusions. The results showed: Balinese ethnic social integration grows well because of the awareness that the Balinese as immigrant ethnic groups even though they were in power but due to the times and the history of the kingdom does no longer exist, the Balinese ethnic who are ethnic of minorities in this village are aware of the immigrant population and must submit to the culture, norms, ethical values possessed by the Sasak tribe as the majority and the owner of cultural capital. Associative social interaction is as a potential to support harmony in society. Peacefulness is in life of the community, and of the people, although there are various differences such as religious differences, but there is mutual tolerance embedded in the hearts of citizens.